Acid sphingomyelinase – a regulator of canonical transient receptor potential channel 6 (TRPC6) activity. Issue 6 (22nd August 2019) - Zeitler, Stefanie; Ye, Lian; Andreyeva, Aksana; Schumacher, Fabian; Monti, Juliana; Nürnberg, Bernd; Nowak, Gabriel; Kleuser, Burkhard; Reichel, Martin; Fejtová, Anna; Kornhuber, Johannes; Rhein, Cosima; et al.
Abstract: Recent investigations propose the acid sphingomyelinase (ASM)/ceramide system as a novel target for antidepressant action. ASM catalyzes the breakdown of the abundant membrane lipid sphingomyelin to the lipid messenger ceramide. This ASM‐induced lipid modification induces a local shift in membrane properties, which influences receptor clustering and downstream signaling. Canonical transient receptor potential channels 6 (TRPC6) are non‐selective cation channels located in the cell membrane that play an important role in dendritic growth, synaptic plasticity and cognition in the brain. They can be activated by hyperforin, an ingredient of the herbal remedy St. John's wort for treatment of depression disorders. Because of their role in the context of major depression, we investigated the crosstalk between the ASM/ceramide system and TRPC6 ion channels in a pheochromocytoma cell line 12 neuronal cell model (PC12 rat pheochromocytoma cell line). Ca 2+ imaging experiments indicated that hyperforin‐induced Ca 2+ influx through TRPC6 channels is modulated by ASM activity. While antidepressants, known as functional inhibitors of ASM activity, reduced TRPC6‐mediated Ca 2+ influx, extracellular application of bacterial sphingomyelinase rebalanced TRPC6 activity in a concentration‐related way. This effect was confirmed in whole‐cell patch clamp electrophysiology recordings. Lipidomic analyses revealed a decrease in very long chain ceramide/sphingomyelin molar ratio after ASM inhibition, which was connected with changes in the abundance of TRPC6 channels in flotillin‐1–positive lipid rafts as visualized by western blotting. Our data provide evidence that the ASM/ceramide system regulates TRPC6 channels likely by controlling their recruitment to specific lipid subdomains and thereby fine‐tuning their physical properties. Abstract : Sphingomyelin is cleaved to ceramide by acid sphingomyelinase (ASM), which is located at the inner membrane of lysosomes and is claimed to translocate to the outer leaflet of the plasma membrane. Produced ceramide clusters to ceramide‐enriched microdomains at the plasma membrane, called lipid rafts, that induce the reorganization of canonical transient receptor potential channels 6 (TRPC6) distribution and stabilize TRPC6 channel function. In the presence of functional inhibitors of ASM activity or specific ASM inhibitor 1‐aminodecane‐1, 1‐bisphosphonic acid (ARC39), ASM is detached from the lysosomal membrane and degraded. This results in a decrease in ceramide/sphingomyelin molar ratio, resulting in changes in TRPC6 plasma domain distribution that reduces TRPC6 channel activation.